Nurses’ Perception of The Implementation of Patient Safety in the Inpatient Ward of a Teaching Hospital - Setiawan Setiawan (Journal of Global Pharma Technology, 2020)
Patient safety is a complex system to prevent injuries caused by mistakes and it allows the nurse to consider taking action or not to deal with the problem of patient safety. The purpose of this study was to explore the nurses’ perceptions of the implementation of patient safety in the inpatient ward of a teaching hospital. A qualitative study was used. The sample consisted of 20 nurses who were involved in a focus group discussion for 70 minutes. The data was analyzed using content analysis as guided by Collaizi. This research found 5 themes that included events almost causing harm to the patients during shifts, obstacles related to reporting events, information about events that should be reported, primary concerns regarding patient safety and habits done to reduce the risk of making mistakes. The implementation of patient safety still needs to be improved due to the lack of perception among the nurses. Patient safety occupies an important position in the health services provided and it plays an important role in the perception of the nurse.Keywords: Inpatient ward, Nurse perception, Patient safety.